The Impact of Social Anxiety on Occupational Participation in College Life. (2nd January 2017) - Clarke, Jenny; Fox, Jackie
ABSTRACT: Social anxiety is a reality for many college students. This study explored the impact of social anxiety on the occupational participation in daily life of six Irish students. Semi-structured interviews were used to explore participants' daily routines, coping mechanisms, and interaction with the environment. The study aims to inform occupational therapists, academics, and other healthcare professionals of the impact of the condition on the daily life of college students. Qualitative data analysis showed that participants described negative beliefs about themselves and had concerns about how they were perceived by others. This affected their ability to fully participate in the student role.